AI- and AR-Assisted 3D Reactivation of Characters in Paintings - Naai-Jung Shih (Heritage)
Ancient paintings are an intangible window to the economy, politics, and customs of the past. Their characteristics have evolved or were made obsolete, with only limited contemporary connections remaining. This research aims to preserve and to interact with characters in 2D paintings to evolve their cultural identity through combining AI and AR. The scope of this research covers traditional Chinese paintings archived by the National Palace Museum in digital collections, mainly “New Year’s Market in a Time of Peace”. About 25 characters were used for training and 3D reconstruction in RODIN®. The models were converted into Augment® and Sketchfab® platforms as reactivated AR characters to interact with new urban fabrics and landscapes. Stable Diffusion® and RODIN® were successfully integrated to perform image training and reconstruct 3D AR models of various styles. As a result, interactions were conducted in two ways: in a mixed context with mixed characters in a painting and in a familiar context in the real world with mixed characters. It was found that AR facilitated the interpretation of how the old urban fabric was arranged. Using AI and AR is a current issue. Combining AI and AR can activate ubiquitous preservation to perform recursive processing from diffused images in order to reconstruct 3D models. This activated heritage preservation method is a reasonable alternative to redefining intangible subjects with a new and evolved contemporary cultural identity.